Implementation of PAI Teacher's Professional Competence in Improving Student Learning Outcomes at SMP N 5 Negeri Agung, Way Kanan - Ayu Alawiyah; Ayu Wahyuni; Yasir Adibroto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This study aims to: (1) describe the implementation of teachers' professional competencies at SMPN 5 Negeri Agung, (2) analyze students' learning outcomes, and (3) identify supporting and inhibiting factors for improvement. The method used is a phenomenological approach with the type of field research, through observation, interview, and documentation techniques. The results show that teachers' professional competence is still not optimal. Some teachers have not met academic qualifications and do not fully understand their duties and responsibilities. This has an impact on students' learning outcomes which are still low. Administratively, learning is running, but not functionally effective. Supporting factors include teachers' academic qualifications and professional awareness. Meanwhile, inhibiting factors include lack of facilities, teacher discipline, and lack of training and coaching. In conclusion, the implementation of teachers' professional competence at SMPN 5 Negeri Agung is not optimal and affects the low learning outcomes. Therefore, improving teacher competence is needed to support the success of students.